Cortical Demyelination in Multiple Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Cortical demyelination in CNS inflammatory demyelinating diseases is reviewed in an editorial and in a study by Moll NM et al (Neurology 2008;70:336-343).